HATE CRIMES IN SOCIAL MEDIA: A CRIMINOLOGICAL REVIEW - Nelufer Yesmen; Arnab Naha; Sumona Sharmin (International Journal of Social Science, 2023)
Hate crime in social media is a common phenomenon around the world. Hate crime against different races, minorities, and ethnic people or groups is now spreading via social media platforms in form of hate speech. The anonymity of the internet user and the availability of the internet make this crime very easy to commit by the offender. This paper aims to find out the targets of hate crime in social media and its effect on the victims. The people who are victimized by hate crime in social media because of their race, gender especially female and religious minority. The study has done by secondary data analysis. Hate crime in social media has a devastating effect on the victim both physically and mainly psychologically which makes them mentally inferior, degradation of self-esteem, and also create a fear of violence in their mind. The existing laws against hate crime in social media should be implemented more precise way and different types of detection methods should be applied to detect the offenders. This paper can be helpful to increase awareness about hate crime in social media which is unnoticed by many researchers in our country and can lead a way to stop victimization in social media platforms.